Effect of conducting polymer layer on microwave absorption properties of BaFe12O19TiO2 composite. Issue 2 (30th October 2012) - Akman, O.; Durmus, Z.; Kavas, H.; Aktas, B.; Kurtan, U.; Baykal, A.; Sözeri, H.
Abstract Ba‐hexaferrite (BaM) particles, synthesized by a sol–gel route, have been mixed with TiO2 powders with different mass ratios. The obtained BaMTiO2 composites have been coated with a conducting polymer layer of polypyrrole (PPy). Structural, magnetic and microwave absorption properties of the PPy‐coated and uncoated BaMTiO2 composites have been investigated by X‐ray diffractometry (XRD), scanning/tunneling electron microscopy, magnetization, and near‐field microwave measurements in the frequency range of 8–18 GHz. The dielectric loss of the PPy‐coated composites appeared to be higher compared to the uncoated samples in the whole frequency range. A single matching frequency was observed for each of the coated and uncoated samples in the frequency range between 16 and 18 GHz. Despite their relatively low absorption properties of uncoated composites (∼−30 dB), PPy‐coated ones have wide absorption bandwidths at −20 dB. The main absorption mechanism in all samples, coated and uncoated, is dielectric loss.